LATERAL DIFFUSION LPE GROWTH OF SINGLE CRYSTALLINE SILICON FOR PHOTOVOLTAIC APPLICATIONS - Li, Bo (My University, 2012)
A modified liquid phase epitaxy (LPE) technique, called lateral diffusion LPE (LDLPE), is invented for low cost and high efficiency solar cell applications. Potentially, LDLPE is able to produce single crystalline silicon wafers directly from the raw material, rather than cutting wafers from single crystalline silicon ingots, therefore reducing the cost by avoiding the cutting and polishing processes.
By using a traditional LPE method, the silicon is epitaxially grown on the silicon substrate by cooling down the saturated silicon/indium alloy solution from a high temperature. The silicon precipitates on the substrate since its solubility in the indium solvent decreases during the cooling process. A SiO2 mask is formed on the (111) substrate with 100µm wide opening windows as seedlines. Silicon is epitaxially grown on the seedline and forms thick epitaxial lateral overgrowth (ELO) layers on the oxide mask. The ELO layers are silicon strips with an aspect ratio of 1:1 (width: thickness), approximately. The strip grows both laterally in width and vertically in thickness.
The concept of LDLPE is to intentionally block the silicon diffusion path from the top of the seedline, but leave the lateral diffusion path from the bulk indium melt to the seedline. Theoretically, by using the LDLPE method, the silicon strip should have a larger aspect ratio, because the laterally growth in width is allowed but the vertical growth in thickness is limited. In addition, single crystalline silicon wafers can be achieved if the strip grows continuously.
A graphite slide boat is designed to place a plate over the seedline to block the diffusion path of silicon atoms from the top of the seedline. After one growth cycle, silicon strips grown by LDLPE are wider than LPE strips but have similar thicknesses. The aspect ratios are increased from 1:1 to a number larger than 2:1. A Monte-Carlo random walk model is used to simulate the change of LDLPE strip aspect ratio caused by placing a plate over the seedline.
Wetting seedline by indium melt is very critical for a successful growth. Due to the small space between the plate and seedline and the surface tension of the indium melt, the indium melt cannot flow into the small space. A pre-wetting technique is used to fill the space prior to loading the graphite boat into the tube furnace and solve the wetting problem successfully.
The structure of a LDLPE silicon strip is characterized by X-ray diffraction. The electrical properties are characterized by Hall Effect measurement and photoconductive decay measurement. LDLPE silicon strips are (111) orientated single crystal and are the same orientation as the substrate. For the growth temperature of 950°C, the LDLPE strip has an estimated effective minority carrier lifetime of 30.9µs. The experimental results demonstrate that LDLPE is feasible for photovoltaic application if continuous growth and scaling up can be achieved.
Keywords: Liquid phase epitaxy; single crystalline silicon; photovoltaics; solar cells; lateral diffusion; Electrical and Electronics; Electronic Devices and Semiconductor Manufacturing; Semiconductor and Optical Materials; Electrical and Electronics